Effectiveness of Activity Book Media in Improving Writing Skills in Severly Deaf Children - Deliza Febrianty; Zulmiyetri Zulmiyetri; Damri Damri; Setia Budi (Universitas Muhammadiyah Enrekang, 2024)
This research aims to prove whether activity book media in improving the writing skills of children with severe hearing impairment, especially writing simple SPO sentences at SLB Budi Karya, Limapuluh Kota Regency. The activity book media is in the form of a 2-dimensional media book containing modified sentence pattern exercises to help students improve their writing skills. This research uses a quantitative approach with the Single Subject Research (SSR) experimental method with an A-B-A design, as well as data analysis using visual graphs that include data obtained during observation of A-B-A conditions into graphs. The results of research on the effectiveness of activity book can improve writing skills, especially writing simple sentences in class X deaf children at SLB Budi Karya Limapuluh Kota Regency.